La detención como medida cautelar prevista en el código orgánico integral penal del Ecuador - Samaniego Ochoa, Rosemberg Efraín (2016)
This legal research includes legal legal content, addresses a subject of vital importance in the criminal law with regard to the detention for investigation. This research was carried out in the legal field of public law, specifically on the shortcomings that exist in the Criminal Code of Ecuador Integral. Detention for investigative purposes is one of the precautionary measures that criminal law provides, obviously this measure is considerably drastic, since it affects freedom as one of the fundamental rights that people have; and also, it does affect our integrity contradicting the presumption of innocence established in our supreme law. I would say that I consider insufficient the duration of detention for the purpose of research, it is indisputable that in such a short time research effectiveness will not be achieved. Expired, the detainee must be released immediately if the investigation has not been successful, except in the case that they had obtained the elements of proof required for the initiation of the preliminary investigation had emerged procedural budgets of the provisional arrest warrant. As mentioned above, it is necessary to establish in the current Criminal Law that should not meet the necessary elements for the criminal charges the suspect or has not completed the investigation, that period can be extended to 24 hours, and even You can order the appearance of the suspect as necessary to provide evidence or dismiss their presumption; all this, according to the principles established in the Constitution, as a possible solution to the given problem as ineffective injunction detention for investigation under the Code of Criminal Integral situation creates legal uncertainty and possible escape from justice.